Exploring University Students’ Creative Thinking Through Digital Mind Maps - Hidayati, Nurkhairo; Fitriani, Apriza; Saputri, Wulandari; Ferazona, Sepita (Journal of Turkish Science Education, 2024)
Creative thinking is an unorthodox way of thinking to produce fresh and new ideas. Creative thinking can be trained using innovative learning strategies. This study aimed to explore creative thinking aspects in the Digital Mind Maps (DMM) created by Universitas Islam Riau, Indonesia, students who were enrolled in Human Anatomy and Physiology course. A rubric containing four aspects of creative thinking, namely fluency, flexibility, originality, and elaboration. The result of the analysis showed that fluency obtained the highest score (95.64) of all aspects and the lowest score was reported by elaboration (61.43). Findings from this study suggest that students’ DMM can be used to determine their creative thinking level because DMM contain distinguished creative thinking details. Based on the results, it can be concluded that the participants’ creative thinking has been properly developed. Therefore, it is advisable for lecturers to use DMM to monitor the development of their students’ creative thinking.